Temporal bone dissector : the interactive otology reference - Blevins, Nikolas H; Mosby-Year Book (St. Louis : Mosby, 1998)
(Producer) Interactive program for learning the surgical anatomy of the ear. Through four modules the viewer can dissect the temporal bone, view CT and MRI scans of the ear (as well as 3-D computer ganerated models), and observe procedural videos that illustrate the actual appearance of the anatomy in a surgical setting.
Title from disc label
Copyright date on guide: 1997
CD is avaiable at Koleksi Media, Perpustakaan HUKM
Nikolas H. Blevins, Robert K. Jackler, Christine Gralapp.
System requirements: Mac 68040 or faster processor (Power PC recommended); (thousands strongly recommended).
Syestem requirements: IBM or compatible PC, 482/25 or faster processor; 16MB RAM; Windows 3.1 or later; SVGA 640 x 256 colors (16 bit strongly recommended); sd. card; 2x or faster CD-ROM drive
Keywords: Temporal Bone -- anatomy & histology -- atlases -- CD-ROM; Temporal Bone -- surgery -- atlases -- CD-ROM; Ear -- anatomy & histology -- atlases -- CD-ROM; Dissection -- atlases -- CD-ROM